Air-breathing versus conventional polymer electrolyte fuel cells: A parametric numerical study. (1st July 2022) - Calili-Cankir, Fatma; Ismail, Mohammed S.; Ingham, Derek B.; Hughes, Kevin J.; Ma, Lin; Pourkashanian, Mohamed
Abstract: Two mathematical models have been built for air-breathing and conventional polymer electrolyte fuel cells to explore the reasons affecting the cell performance. A parametric study has been conducted to (i) investigate how each type of fuel cells responds to changes in some key parameters and (ii) consequently obtain some insights on how to improve the performance of the air-breathing fuel cell. The conventional fuel cell significantly outperforms the air-breathing fuel cell and this is due to substantially higher forced convection-related heat and mass transfer coefficients associated with the conventional fuel cell as compared with natural convection-related heat and mass transfer coefficients associated with air-breathing fuel cell. The two types of fuel cell respond differently to changes in porosity and thickness of gas diffusion layer: the conventional fuel cell performs better with increasing porosity of gas diffusion layer (from 0.4 to 0.8) and decreasing thickness of gas diffusion layer (from 700 to 100 μm) while the air-breathing fuel cell performs better with decreasing porosity and increasing thickness of gas diffusion layer. Further, the air-breathing fuel cell was found to be more sensitive to membrane thickness and less sensitive to electrical resistance compared to conventional fuel cell. Highlights: Two numerical models were developed for air-breathing and conventional PEFCs. The impact of key design parameters on the cell performance was investigated. The conventional PEFC significantly outperforms the air-breathing PEFC. The fuel cells respond differently to changes in the GDL porosity and thickness. They perform better with decreasing membrane thickness and electrical resistance.